EVALUASI PENYELENGGARAAN PELAKSANAAN PROGRAM PEMBANGUNAN EKONOMI DAN KELEMBAGAAN KAMPUNG (PROSPEK) DI PROVINSI PAPUA - Yoel Wamafma (JURNAL KEBIJAKAN PUBLIK, 2020)
The purpose of this research is to: (1) (evaluating the implementation of the 2014-2018 Institutional and Economic Prospects, and knowing the obstacles, support and problem-solving methods appropriate for the implementation of the 2014-2018 Institutional and economic Prospect of Papua. The results of the study show that: (1) Evaluation of Prospects in Developing and Economic in 2014-2018 viewed from the context of the evaluation, this prospect is really very useful, according to the program / activity starting from the implementation planning stage to the accountability report carried out by the community itself. Evaluation of input, the implementation of the prospect is carried out with instructions delivered by the companion and carried out in accordance with the direction of the companion. Process evaluation, the allocation funded by prospects is used for the basic needs of the community in which building infrastructure, the economy and also financing institutional activities. (2) Factors that serve and support, support and appropriate solutions to carry out evaluation prospects in the institutional and economic fields of 2014-2018. That is, there are still village heads / lurah, assistants at the time of fund issuance often cut and prospects that are the right of the community, lack of socialization carried out so that the beneficiaries carry out activities not in line with expectations and are not sustainable. the technical guidelines must be issued early in the year so that the process in the field can go according to plan.